The natural history of hypertension in older adults : a study of two Finnish generational cohorts born 20 years apart - Lääti, Adriana; Teppo, Konsta; Vire, Jenni; Viitanen, Matti; Langén, Ville (Taylor & Francis, 2025)
Background: We conducted a comparative analysis of hypertension prevalence, progression, and treatment in two Finnish population-based cohorts comprising older adults born 20 years apart. The study covered data from pre- and post-HYVET Study eras and spanned the onset of the COVID-19 pandemic.
Methods: All 70-year-old home-dwelling citizens of Turku, in Southwest Finland, were invited to participate in the survey in 1990 (1920-born TUVA cohort) and in 2010 (1940-born UTUVA cohort) with a 25-year follow-up plan. The analyses included those with available data for systolic and diastolic blood pressure (BP), yielding 1015 TUVA and 888 UTUVA participants at baseline. Biomarkers associated with BP were analysed with t- and chi-square tests.
Results: At baseline, 83.4% of TUVA and 74.3% of UTUVA participants had uncontrolled BP, with respective antihypertensive medication usage at 36.0% and 55.9% (p < .001 for both between-cohort differences). Systolic BP exhibited an inverted U-shaped trajectory, with TUVA initially 7.8 mmHg higher at 155.4 mmHg than UTUVA (p < .001). However, by the ages 80-82, the difference in systolic BP trajectories between the cohorts was attenuated to 4.0 mmHg (p = .03). Diastolic BP differences were less clinically significant. UTUVA demonstrated higher use of all five conventional antihypertensive categories than TUVA (p ≤ .02 for all categories).
Conclusions: In the early years of older adulthood, the 1940-born cohort showed a positive trend in hypertension management, yet maintained a 74.3% baseline rate of uncontrolled BP. Furthermore, by the ages 81-82, the benefits observed over the 1920-born cohort had lessened, influenced by the COVID-19 pandemic or other lasting factors. Heightened efforts to improve hypertension treatment in older adults remain crucial in the post-HYVET era.